Attitudes towards Spoken and Written Spanish Language of the United States (2019)
In this paper we analyze attitudes towards spoken and written Spanish Language of the United States. The study is based on a questionnaire submitted to native Spanish speakers from different countries of the Hispanic world through an online collection instrument called Survey Monkey. A total of 110 Spanish speakers from Spain, Colombia, Peru, Argentina, Cuba, Puerto Rico, Guatemala, México and Chile participated. The results show both the knowledge and attitudes that these speakers have about Spanish language in the United States, as well as some signs of vitalization and development of Spanish in that country.